EP.WE.429Surgery during the COVID-19 pandemic: Are we obtaining informed consent?. (28th October 2021) - Robinson, Emily; Ayathamattam, Joseph; Harris, Holly; McFall, Malcolm
Abstract: Background: It was estimated that 1 in 4 inpatients with COVID-19 acquired the virus whilst admitted in December 2020. Surgical patients that contract COVID-19 have poor outcomes, with mortality rates as high as 24% and risk of pulmonary complications as high as 50%. The Royal College of Surgeons of England published COVID-19 consenting guidelines in June 2020. Aims: To identify the proportion of surgical patients who were informed of the risk of acquiring COVID-19 during the consenting process at two District General Hospitals. Methods: The consent forms of 220 surgical patients who had either elective or emergency surgery during the second COVID-19 lockdown were reviewed retrospectively (1/11/2020-20/11/2020). This included General Surgery, Trauma and Orthopaedics and Urology. Patients with incomplete notes or who lacked capacity were excluded. Results: In total, 193 patients were included. We found that 41.5% of patients were consented for the risk of acquiring COVID-19 peri-operatively. This did not vary significantly between elective and non-elective patients. Conclusions: Our study shows that current practice does not meet national recommendations. In order to provide informed consent, surgeons must engage in emerging research regarding the local prevalence of COVID-19 and the implications of infection during the peri-operative period. Only with this knowledge, will surgeons be able to balance the risks and benefits on a case by case basis, to provide the patient with necessary information for consent. We recommend that trusts adopt a COVID-19 consenting policy, as part of the pre-operative assessment.